Pemanfaatan Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi oleh Guru Sekolah Dasar - Irma Sari Sinaga; Faizal Chan; Muhammad Sofwan (Edumaspul: Jurnal Pendidikan, 2020)
The purpose of this study is to describe the use of information and communication technology-based learning media (computers / laptops, LCD projectors and internet networks) by elementary school teachers. This study uses a qualitative research approach to the type of phenomenological research. The sampling technique used was purposive sample. The main data sources in this study were Vc and 3a grade elementary school teachers no. 55/I Sridadi. Data collection techniques used in this study were observation, interviews and documentation. Data analysis techniques using Miles and Huberman's theory consisting of data reduction, data presentation, and data verification. The results of this study indicate that the teacher has used computer / laptop media, LCD projectors, and internet networks. The teacher uses the laptop as a data storage medium for learning activities such as learning pictures and videos, as a media for audio and visualization of learning materials such as pictures, learning videos, and ice breaking videos, and processing learning software programs such as Microsoft PowerPoint. Projector LCD is used to display information from images, and learning videos. Internet networks are used to find sources of information from Google or YouTube.